Online Fault-Tolerant Onboard Aeroengine Model Tuning Structure - Shuiting Ding; Ye Yuan; Naiyu Xue; Xiaofeng Liu (International Journal of Aerospace Engineering)
Online onboard aeroengine models (OBEMs) have been widely used in health management, fault diagnostics, and fault-tolerant control. A mismatch between the OBEM and the actual engine may be caused by a variety of factors such as health degradation or sensor fault and may influence the effectiveness of the systems mentioned above. However, mismatch caused by unpredictable sensor fault is hardly distinguished from that caused by health degradation through the tuning process. A fault-tolerant OBEM tuning structure is provided to perform the online tuning function when health degradation and sensor fault coexist. This system includes three parts that include improved fault diagnostics and isolation (IFDI), a fault-tolerant OBEM tuning system (FTOTS), and a channel switching module. IFDI is used to distinguish the cause of mismatch and provide fault information, a FTOTS is used to complete an online tuning process based on information obtained from the IFDI, and the channel switching module is used to switch the working process from the IFDI to the FTOTS. Several simulation results show that this system is able to distinguish the causes of mismatch and complete online tuning in the case of sensor faults.